Hyperbilirubinemia treatment of neonatus in dr. Soetomo hospital surabaya - Hosea, Mellisa Kristanti; Etika, Risa; Lestari, Pudji (Folia Medica Indonesiana, 2016)
Hyperbilirubinemia is a condition of high levels bilirubin accumulating in blood and known as jaundice, a yellow coloration of the skin, sclera and nails. Hyperbilirubinemia is a problem that often occurs in newborns. Patients with neonatal hyperbilirubinemia are treated with phototerapy and exchange transfusion. The purpose of this study was to identify the hyperbilirubinemia treatments on neonatal in Dr. Soetomo Hospital Surabaya. Medical records were used to collect information on hyperbilirubinemia status and type of treatments in 2010. Inclusion criteria were used to select samples in this study. All hyperbilirubinemia patients (100 neonates) were treated with phototherapy, in which 32% of them got the treatment for less than 24 hours; and 68% got the treatment more than 24 hours. After treatment, 100% patients cured. Hyperbilirubinemia neonates in RSUD Dr Sutomo were treated with phototherapy and the treatment was successful.